Safety of transradial cardiac catheterization in patients with end‐stage liver disease. Issue 3 (3rd July 2013) - Jacobs, Evan; Singh, Vikas; Damluji, Abdulla; Shah, Neil R.; Warsch, Jessica L.; Ghanta, Ravi; Martin, Paul; Alfonso, Carlos E.; Martinez, Claudia A.; Moscucci, Mauro; Cohen, Mauricio G.
<x xml:space="preserve">Abstract</x> Background Transradial access may be advantageous for patients with end‐stage liver disease (ESLD) who need to undergo left heart catheterization (LHC). We aimed to assess the safety of transradial cardiac catheterization in patients listed for orthotopic liver transplantation. Methods This is a retrospective analysis of consecutive adult patients with the diagnosis of ESLD, who underwent LHC via transradial access as part of a pre‐operative liver transplantation evaluation. All the patients also underwent right heart catheterization (RHC) via brachial or femoral vein. The primary outcome measure was procedure‐related major bleeding. Secondary outcomes included access site minor bleeding, in‐hospital mortality, radial access failure, and acute kidney injury. Results A total of 82 consecutive patients with ESLD, who underwent LHC via transradial access, were enrolled in the study. All patients also underwent RHC (n = 45 via brachial and n = 37 via femoral vein). The median age was 59 (54, 67) years old, and 58% were male. History of coronary artery disease or heart failure was present in 17% of patients. The median MELD score was 19 (13, 24.5), baseline hemoglobin was 10.5 mg/dL (9.4, 11.8), INR was 1.4 (1.2, 1.8) and platelets were 74, 000 (53, 000, 117, 000)/mm3. The most common etiology of liver failure was viral hepatitis (51%), followed by alcoholic cirrhosis (24%) and non‐alcoholic steatohepatitis (21%). Angiographically significant coronary artery disease was present in 17 (21%) patients. Major bleeding and acute kidney injury each occurred in two patients (2.4%). There were no instances of vascular complications. There were no deaths attributable to complications from cardiac catheterization. Conclusion Upper extremity right and left heart catheterization appears to be a safe method to evaluate coronary anatomy and hemodynamics in a severely ill population of patients with ESLD awaiting transplant. © 2013 Wiley Periodicals, Inc.